An electrical super-insulator prototype of 1D gas-solid Al2O3 nanocell. (September 2017) - Xin, Meng; Chang, Zhengshi; Luo, Haiyun; Zeng, Rong; Zhang, Guanjun; Lei, Qingquan
Abstract: High electric breakdown strength of insulating materials is essential to improving the reliability of the electricity grid, reducing the size of electric devices, saving energy, protecting the environment, and reducing costs. Traditionally, dielectric breakdown strength is increased by exploiting its dependence on the thickness of the dielectric material, based on the electron impact ionization and avalanche theory by Townsend (1900) and Seitz (1949) [9]. However, at present there has been little research addressing the role of the transverse dimension (perpendicular to the direction of the electric field) in the avalanche breakdown process, and no results about research in nanoscale. An insulation breakdown prototype of a 1D nanocell was constructed. It consisted of an air-column and Al2 O3 solid wall. Based on the analysis and comparison between nanocell geometrical dimensions and avalanche physical dimensions, it was found that the properties of the 1D nanocell diverges from the gas/solid discharge theories of Townsend and Seitz. Along with the I-V results of 1D nanocell by C-AFM (Conductive-Atomic Force Microscope), it was demonstrated that electrical breakdown cannot be caused by electron avalanche in 1D nanocell. The discharge properties of Al2 O3 NPT (nano pore template) with nanocells array and when it inserted into the air gap as a barrier were studied to further demonstrate the capability of 1D nanocells on the electrical characteristic of macroscale material. Results showed that the scale effect of nanocells have an obvious role in improving the dielectric breakdown voltage, with singular discharge phenomena identified. This study proposes a new super-insulator prototype of 1D nanocell and supplies a novel thought for constructing high performance nanostructured dielectrics for more wide applications, and provides a scientific basis on the interconnection among Micro-Meso-Macro scales. Graphical abstract: A new insulation prototype of 1D nanocell consisting of gas and solid was shown to be useful to improve dielectric breakdown strength. The role of the transverse dimension (perpendicular to the direction of the electric field) in electron avalanche breakdown process is important especially in nanoscale, and accompanied with singular discharge phenomenon existing. Highlights: We constructed a super-insulation prototype by the 1D nanocells. Breakdown voltage of the NPT is greatly higher than that of the air gap. 2–5 The single nanocell fails to meet the classical breakdown criterion. First reported the role of the transverse dimension in the avalanche breakdown.